DIGITAL LOGISTICS TRANSFORMATION AS A DRIVER OF INTERNATIONAL TRADE COMPETITIVENESS IN ENTREPRENEURSHIP WITHIN THE GLOBAL ECONOMY (International scientific-electronic journal “Pioneering studies and theories”, 2026)
In an era defined by accelerating technological disruption and the deepening integration of global markets, the digital transformation of logistics has emerged as a strategically decisive determinant of international trade competitiveness for entrepreneurial firms. The present study critically examines the mechanisms through which digital logistics transformation functions as a principal catalytic force in reshaping the competitive architecture of firms engaged in cross-border commerce within the contemporary globalized economy. Situated within the broader theoretical context of the Fourth Industrial Revolution which marks a decisive transition from the information age to the age of digital intelligence the logistics sector is currently undergoing a profound and irreversible structural reconfiguration, propelled by the rapid proliferation and institutional embedding of digital economy instruments across global value chains. Drawing upon a systematic and comparative analysis of scholarly contributions and practitioner-oriented perspectives across multiple national and regional contexts, this study investigates the transformative implications of progressively adopting a constellation of advanced digital modern technology like artificial intelligence, Big Data, internet of things, cloud technologies, and mostly multi-party logistics services with first-party logistics (1PL) through fifth-party logistics (5PL).